Comparison of Composite Quality from PP Plastic with Recycled HDPE Through The Screw Extruder Process - Zulnazri, Z; Atmaja, W; Maliki, S; Muarif, A; Noviansyah, F; Ramadhan, C (International Journal of Engineering, Science and Information Technology, 2021)
This study examines the composite quality of PP and HDPE plastic waste materials using Microfiber Oil palm empty fruit bunches (OPEFB) as filler, the fiber used is 90 Âµm. The ratio of matrix: filler used is 60:40 and 70:30 for each type of PP and HDPE polymer. The method used is a melt blending screw extruder, where plastic and fiber materials are dissolved with a compatibilizer and then melt blended in an extruder by providing temperatures of 160 and 170 oC. Tensile tests showed the strength of the PP composite with a filler ratio of 60:40 and 70:30, respectively, of 313.25 N and 336.35 N, while the HDPE composite with a filler ratio of 60:40 and 70:30, respectively are 392.93 N and 187.90 N. The maximum force required to break HDPE composites reaches 21.10 Mpa while for PP composites it reaches 18.56 Mpa. From the morphology of the PP and HDPE composite samples, the overall surface structure of HDPE looks regular with a width from 1 to 13.5 mm. The PP composite shows a uniform and regularly arranged surface structure and the bond between the fibers and the filler looks more compatible but the surface pores are rougher. Heat resistance can be seen from the melting point of PP composites which can reach 163.81oC while HDPE composites only reach 134.21oC.